Photorelease of GABA with visible light using an inorganic caging group - Rial Verde, Emiliano; Zayat, Leonardo; Etchenique, Roberto; Yuste, Rafael (Frontiers in Neural Circuits, 2008)
We describe the selective photorelease of γ-amino butyric acid (GABA) with a novel caged-GABA compound that uses a ruthenium complex as photosensor. This compound (“RuBi-GABA”) can be excited with visible wavelengths, providing greater tissue penetration, less photo-toxicity, and faster photorelease kinetics than currently used UV light-sensitive caged compounds. Using pyramidal neurons from neocortical brain slices, we show that RuBi-GABA uncaging induces GABA-A receptor-mediated responses, has no detectable side effects on endogenous GABAergic and glutamatergic receptors and generates responses with kinetics and spatial resolution comparable to the best caged GABA compounds presently available. Finally, we illustrate two potential applications of RuBi-GABA uncaging: GABA receptor mapping, and optical silencing of neuronal firing.